GEOGRAPHIC RHYTHM STUDY SCULPTURE AND CARVING ART INDUSTRY JEPARA DISTRICT CASE STUDY IN MULYOHARJO VILLAGE - Angger Bagus Iswanto; Sarwono Sarwono; Rita Noviani (Universitas Sebelas Maret (UNS), 2020)
The purpose of this study is to find out geography rhythm procurement of raw materials, marketing destination, and problems with production factors sculpture and carving industry in the center of the sculpture and carving industry center in Mulyoharjo Village, Jepara District. This study uses a qualitative descriptive method. The respondent is a sculpture and carving industry entrepreneur in Mulyoharjo Village whose population is 104 industries and 30 industries are sampled. Data collection by interview, documentation and observation. Data analysis used a descriptive qualitative interactive model technique. The results of the study concluded that 86.6% of the industries experienced capital problem,73.3% of the industries experiences raw material problem, 66.6% of the industries experiences marketing problem, and 73,3% of the industries experiences finding workers problem. The most difficult workforce to find is engraver because absence of engraver regeneration. The raw materials used are teak wood and tamarind. In 1990 the raw material came from Jepara. In 1997-2005 the origin of raw materials expanded into the Java Island region. In 2006-2019 the origin of raw materials moved out of Java. The current availability of wood is not experiencing scarcity but the price is increasing. In 1990-1992 the destination areas for product marketing were in the Jepara Regency area only. In 1993-1995 product marketing could reach big cities in Indonesia. Marketing of products to international markets occurred in 1996 until now. In 2013 the number of exports increased with a value of 7,505,772.91 US . In 2014 to 2018 the number of exports decreased.